INTEGRASI KURIKULUM KEWIRAUSAHAAN DALAM PENDIDIKAN TINGGI SEBAGAI UPAYA MENCETAK LULUSAN SIAP BERWIRAUSAHA: INTERNALISASI NILAI-NILAI ENTREPRENEUR DALAM KONTEKS PENDIDIKAN - Syamsurijal; Wahira (STKIP Subang, 2025)
Higher education institutions face fundamental challenges in preparing graduates who possess not only academic competence but also entrepreneurial readiness to navigate increasingly complex labor market dynamics. This study aims to analyze the conceptual framework of entrepreneurship curriculum integration in higher education oriented toward developing graduates with entrepreneurial mindset and readiness. Using Systematic Literature Review methodology following PRISMA protocol, this research synthesized six relevant peer-reviewed articles from reputable academic databases covering the 2021-2025 period. The findings reveal that distribution of Entrepreneurship Education Programs in Indonesia remains limited and concentrated in dominant institutions, particularly on Java Island. Effective pedagogical models emphasize mentoring approaches, authentic project-based learning, and integration with business communities. Key determinants of program effectiveness include self-efficacy, entrepreneurial intention, subjective norms, and failure attribution learning. The research identifies significant positive correlations between entrepreneurial intention, self-efficacy, and student preparedness for entrepreneurship. Strategic recommendations encompass expanding EEPs distribution nationwide, implementing systematic mentoring models, strengthening institutional capacity, and creating supportive learning ecosystems. This study contributes to entrepreneurship education theory development in developing country contexts while providing evidence-based insights for curriculum design that responds to Generation Z characteristics and contemporary business ecosystem demands.